2004
DOI: 10.1073/pnas.0306266101
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein and apolipoprotein AI increase endothelial NO synthase activity by protein association and multisite phosphorylation

Abstract: NO propagates a number of antiatherogenic effects in the endothelium, and diminished availability has been associated with vascular disease. Recently it has been reported that phosphorylation of endothelial NO synthase (eNOS) at Ser-1179 is required to increase activity in response to stimuli, including high-density lipoprotein (HDL). The current study was undertaken to further examine the mechanism by which HDL activates eNOS and to specifically determine the role of the major apolipoprotein of HDL, apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 38 publications
5
108
0
3
Order By: Relevance
“…AMPK stimulates eNOS activity by phosphorylating eNOS at Ser 1177 and promoting its association with HSP90. Several vasoprotective agents, such as the antidiabetic drug metformin (40), 17␤-estradiol (34), high-density lipoprotein, and apolipoprotein AI (41), have recently been shown to activate AMPK in endothelial cells. Consistent with the previously reported findings (12,16), our results also demonstrated that AMPK is the principal kinase responsible for adiponectin-evoked eNOS phosphorylation at Ser 1177 , eNOS association with HSP90, and NO production in HUVECs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK stimulates eNOS activity by phosphorylating eNOS at Ser 1177 and promoting its association with HSP90. Several vasoprotective agents, such as the antidiabetic drug metformin (40), 17␤-estradiol (34), high-density lipoprotein, and apolipoprotein AI (41), have recently been shown to activate AMPK in endothelial cells. Consistent with the previously reported findings (12,16), our results also demonstrated that AMPK is the principal kinase responsible for adiponectin-evoked eNOS phosphorylation at Ser 1177 , eNOS association with HSP90, and NO production in HUVECs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HDL can stimulate NO production. eNOS activity can be upregulated by HDL through regulation of phosphorylation sites [23]. Different signalling pathways are likely to be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…APOA-I is also involved in the delivery of cholesteryl esters to the liver via scavenger receptor class B type I (SR-BI) [4]. A decreased bioavailability of endothelium-derived NO is an important antecedent to atherosclerosis, and it was recently reported that APOA-I could upregulate the activity of endothelial nitric oxide synthase (eNOS), likely through specific phosphorylation of AMP-activated protein kinase (AMPK) in endothelial cells [5]. However, the intracellular function of APOA-I is largely uncharacterised.…”
Section: Introductionmentioning
confidence: 99%